2023
DOI: 10.1021/acsaem.3c00613
|View full text |Cite
|
Sign up to set email alerts
|

Transition-Metal and Nitrogen-Doped Carbon Nanotube/Graphene Composites as Cathode Catalysts for Anion-Exchange Membrane Fuel Cells

Abstract: Transition-metal and nitrogen-doped graphene-like material and carbon nanotube (M-N-Gra/CNT) composites are prepared, characterized, and used as cathode catalysts in anion-exchange membrane fuel cells (AEMFCs). Melamine as a nitrogen source and cheap iron and cobalt salts as metal precursors are used for doping via high-temperature pyrolysis. The success of doping is proven by several physicochemical analysis methods, and the catalyst materials possess rather similar textural properties. The initial assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 73 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…For instance, our group reported the potential role of Fe and Co doping on graphene/CNT composite catalysts in enhancing the power output of AEMFCs. 38 The prepared composite carbon catalysts showed an excellent ORR activity with a half-wave potential ( E 1/2 ) reaching 0.81 V vs. RHE, and an AEMFC power output of 0.64 W cm −2 was achieved for the bimetallic Fe- and Co-doped catalysts. Another study was reported with Fe- and Co doped mesoporous carbon catalysts applied as cathode materials in AEMFCs.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…For instance, our group reported the potential role of Fe and Co doping on graphene/CNT composite catalysts in enhancing the power output of AEMFCs. 38 The prepared composite carbon catalysts showed an excellent ORR activity with a half-wave potential ( E 1/2 ) reaching 0.81 V vs. RHE, and an AEMFC power output of 0.64 W cm −2 was achieved for the bimetallic Fe- and Co-doped catalysts. Another study was reported with Fe- and Co doped mesoporous carbon catalysts applied as cathode materials in AEMFCs.…”
Section: Introductionmentioning
confidence: 90%
“…In previous studies, we have tested Fe-and Co-based catalysts in an AEMFC using a 10 μm thick Aemion + AEM, but no reports are available with the Aemion+® 15 μm AEM. 38,75,[77][78][79][80] The Aemion+ AEM (10 μm) consists of repeating units of methylated polybenzimidazoles, which offers high stability in AEMFCs by employing the stericcrowding strategy to stabilise the C-2 position of the imidazole group. 81 Also, the thickness of the AEM plays a crucial role in the efficient migration of OH − ions and H 2 O molecules.…”
Section: Aemfc Performancementioning
confidence: 99%
“…One of the first approaches in the preparation of carbonbased catalysts with M-N x sites has been the functionalisation of pre-existing carbon materials using high-temperature pyrolysis in the presence of precursors of transition metal and nitrogen. Various nanocarbon materials, such as carbon black, [13,52,53] carbon nanotubes (CNTs), [54] carbide-derived carbon, [55] graphene, [56] mesoporous carbons [57] and composites of these [58][59][60] have been used as substrates. For doping, a great variety of nitrogen precursors can be employed, along with simple transition metal salts, such as acetates, nitrates or chlorides.…”
Section: Synthetic Approachesmentioning
confidence: 99%
“…There are several reports showing that CoFe-based electrocatalysts perform better than their single-metal counterparts in the AEMFC. [59,60] However, they also contain metallic nanoparticles or characterisation has not been sufficient to clearly state them as DACs. Lilloja et al [180] prepared bimetallic materials using a combination of transition metal salts and 1,10phenanthroline to obtain M-N x sites in the final electrocatalyst.…”
Section: Bimetallic Electrocatalysts For Aemfc Cathodementioning
confidence: 99%
“…From various precious metal-free electrocatalysts for ORR, nanostructured carbon materials doped with nitrogen and transition metals (M–N–C catalysts) have proven to be particularly advantageous, especially in alkaline conditions. , The ORR-active sites in such materials are suggested to be the nitrogen-coordinated atomically dispersed metal centers (M–N x ); in alkaline media also various other nitrogen species, such as pyridinic, graphitic, or pyrrolic nitrogen play a role. Such catalysts are most often prepared either by functionalization of nanostructured carbon materials, e.g., carbon black, carbon nanotubes, carbide-derived carbon, graphene, mesoporous carbons, and composites of these, or by carbonization of organic precursors along with transition metal and nitrogen sources. , Thanks to its low cost and abundance, biomass is frequently used as an organic precursor, while its nature, structure, and chemical composition greatly influence the properties of the resulting carbon materials. , Lignin is an abundant component in plant biomass and a waste product of the paper industry, which due to its high carbon content has often been used as a precursor for the preparation of carbon materials by pyrolysis . Among the other applications, lignin-derived heteroatom-doped and transition metal-containing catalysts have been studied as catalysts for ORR, or as bifunctional electrocatalysts for ORR and the oxygen evolution reaction. …”
Section: Introductionmentioning
confidence: 99%